18x+3(4x-9)=-6x+81

Simple and best practice solution for 18x+3(4x-9)=-6x+81 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x+3(4x-9)=-6x+81 equation:


Simplifying
18x + 3(4x + -9) = -6x + 81

Reorder the terms:
18x + 3(-9 + 4x) = -6x + 81
18x + (-9 * 3 + 4x * 3) = -6x + 81
18x + (-27 + 12x) = -6x + 81

Reorder the terms:
-27 + 18x + 12x = -6x + 81

Combine like terms: 18x + 12x = 30x
-27 + 30x = -6x + 81

Reorder the terms:
-27 + 30x = 81 + -6x

Solving
-27 + 30x = 81 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-27 + 30x + 6x = 81 + -6x + 6x

Combine like terms: 30x + 6x = 36x
-27 + 36x = 81 + -6x + 6x

Combine like terms: -6x + 6x = 0
-27 + 36x = 81 + 0
-27 + 36x = 81

Add '27' to each side of the equation.
-27 + 27 + 36x = 81 + 27

Combine like terms: -27 + 27 = 0
0 + 36x = 81 + 27
36x = 81 + 27

Combine like terms: 81 + 27 = 108
36x = 108

Divide each side by '36'.
x = 3

Simplifying
x = 3

See similar equations:

| 3X+9Y=-18 | | x-3/8-1=x-7/9 | | 8=11p+13 | | 9x^2+23x+4=0 | | -4(p+2)+8=2p(p-1)-7p+15 | | -104=8(p-8) | | 2.3(5-x)=-0.7(1-x) | | -2.05x+1.8(x-3)=6.2 | | -10p-3=-1+2(3p-9) | | X+x+42=180 | | 4x+72-4x=27x-21-4x | | 3x-13=8x+22 | | 6x-3y-4z=-15 | | 15=-20x | | 30x^2+55x+15= | | -27-3x=-x^2+1 | | x+3+4-8=5+7x | | 5(-4+3b)=-125 | | 45t=-30 | | 5n+9=4-4(2n-11) | | 1/3(1-x)-(x+1)/2=-2 | | 6.46+2.3x=1.24x-7 | | 129=3(1+7v) | | .2y-3=.5 | | G(-2)=4(-2)-3 | | (9x-3)/6=5/2 | | y/5-7=-2 | | t^2/2+t^2 | | 13a-45+a= | | 4x+4x(.05)=105.00 | | 62.9296(y-100)+64.9278y=63.546 | | -286=4(1+8r)+2r |

Equations solver categories